Polymorphism for Interleukin-4 (-590 C/T) Promoter: Non-Association with Endometriosis - Rika Hairunisyah; Siti Fatimah (Yayasan Rumah Ilmu Professor, 2022)
Endometriosis is a benign gynecological disorder that often occurs in women of reproductive age, usually characterized by endometrial epithelium and stroma outside their usual location. It is estimated that this disease affects 56% of women worldwide. Various types of cytokines are associated with endometriosis, including interleukin IL-4, which inhibits the production of proinflammatory cytokines that stimulate active B cells and T cell proliferation, the differentiation of B cells into plasma cells. Il-4 promoter region polymorphism (-590C/T) is involved in genetic susceptibility to endometriosis. This study aims to determine whether Gen IL-4 (-590C/T) polymorphism indicates endometriosis. This study is an analytical observational study conducted at the Laboratory of Molecular Biology in Palembang City in August 2021, with the approach of Case-Control study. There were 70 samples divided into two groups, namely 35 cases and 35 controls. Determination of genotypes and alleles using PCR-RFLP and chi-square analyzed data to determine the relationship. The results showed no significant difference. The genomorphism of the Interleukin-4(-590C/T) gene cannot be used to indicate endometriosis susceptibility.